Hungarian Monitoring, 27 February 1988 . [Magyar rádiófigyelő], 1988. február 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Washington on the Panama situation - Pravda on the Afghanistan talks in Geneva Domestic Affairs: - Gromyko's visit - Péter Várkonyi signed this year's barter trade protocols in Moscow - Marjai signed this year's goods barter turnover minutes in Moscow - War crimes case of Imre Finta - Pension reform - Békéscsaba theoretical conference Külpolitika: -Washington a panamai helyzetről - A Pravda a genfi Afganisztán tárgyalásokról Belpolitika: - Gromiko látogatás - Várkonyi Péter Indiában - Marjai Moszkvában aláírta az idei árucsere forgalmi jegyzőkönyvet - Finta Imre háborús bűnösségi ügye - A nyugdíjreform kérdése - Békéscsabai elméleti tanácskozás